Reseach of Control System of Packaging Machine on PLC - Xiao SUN; Hao ZHOU; Xiangjiang LU; Yongbin LIU (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
An automatic control system of sampling package for sample coal is designed according to the realities of sample coal powdery materials which are based on controller (PLC). The system can realize the functions of random sampling, auto-weighting, auto-packaging, and auto-sealing off. It also can adjust waste less, control convenient, zero point self-tuning and dynamics weighing measurement. It can be used in sampling weighing package of sample coal. Various performance indicators can be stably and reliably used in field. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2614